Effect of bio-pesticides and nitrogen on quantitative and qualitative characters of red cabbage (Brassica oleracea var. capitata f. rubra) - THAKUR, DIKSHA; KAUR, DINANTER PAL; KAUR, GURBAKSH; KUMAR, SAGAR; SHARMA, NEHA (The Indian Journal of Agricultural Sciences, 2026)
Red cabbage (Brassica oleracea L. var. capitata f. rubra) belongs to Brassiceae family, is an important exotic and cool season vegetable. The experiment was conducted during the winter (rabi) seasons 2019–2020 and 2020–2021 at the Experimental Farm, Mata Gujri College, Fatehgarh Sahib, Punjab to assess the effect of different doses of nitrogen with various bio-pesticides. Various nitrogen doses along with Trichoderma harzianum, Pseudomonas fluorescens, and neem cake were used as bio-pesticides. Trichoderma harzianum and Pseudomonas fluorescens multiplied very well in gunny bags on farm yard manure in the shade. Water was sprinkled on the gunny bags on a daily basis for 15 days and the microbial population had grown to the point where it was ready for soil application. The treatment N2B2 (125 kg N/ha + Pseudomonas fluorescens @10 g/kg FYM) gave maximum equatorial diameter (15.48 cm), polar diameter (17.80 cm), head yield/plant (1.50 kg), head yield/plot (36.08 kg), biological yield (2.27 kg/plant), harvest index (67.01%), total soluble solids (7.64°B), titratable acidity (0.299%), vitamin A (277.82 mg/100 g), vitamin C (52.25 mg/100 g), shelf life (19.86 days), physiological loss in weight (8.83%), anthocyanin content (34.50 mg/100 g) and moisture content (97.66%). Thus, it was rated as the best treatment resulting in maximum head yield/ha (146.18 q/ha).